Determining the thickness of the Earth's crust in the territory of the Republic of the Niger based on the stochastic interpretation of the gravitational field (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: The territory of the Republic of the Niger and the surrounding countries of West Africa are among the areas where few ground and aero-geophysical surveys have been conducted aimed at studying the Earth's crust in the region. The purpose of this article is to compile ground and satellite data regarding the gravitational field in order to study the Earth's crust based on incomplete geological and geophysical information. The aim of the subsequent interpretation of the detected gravity anomalies is to create an updated map of the thickness of the Earth's crust on the territory of the Republic of the Niger. At the moment, there are several significantly different versions of the crust structure in this area. Methodology: We combined the results of ground gravimetric surveys conducted in the 1960s and the modern digital satellite models of the gravitational field in order to produce a synthetic model of an anomalous field, which can be subsequently interpreted using a common stochastic model with singular sources distributed in the horizontal layer. Results and discussion: We used the results of the interpretation of gravity anomalies based on the stochastic model of the filed sources to make a map of the estimates of the thickness of the Earth's crust for the studied territory and its adjacent regions. The comparison of the produced map with the results of the previous studies of the thickness of the earth's crust, revealed significant difference in the models of the crust, especially in the eastern part of the region. The statistical analysis of the received estimates of the thickness of the Earth's crust and the averages of the terrain shows that these parameters tend to be connected. This indicates partial isostatic compensation for large blocks of the region's crust. The analysis of the thickness of the Earth's crust and the map of the surface geological and tectonic elements on the territory of the Republic of the Niger allowed us to determine the connection between the geodynamic evolution of the crust and the location of the crust-mantle boundary. Conclusions: The synthetic model of the gravitational field reduced to the Bouguer anomaly serves as a reliable basis for solving the problems of regional gravimetric modelling. Based on the results of the stochastic interpretation of the gravitational field of the region we obtained estimates of the thickness of the earth's crust of the studied territory within the accepted model of the layer with random distribution of density heterogeneities. Comparison of the obtained estimates of the thickness of the Earth's crust with the data of the standard crustal model CRUST1 demonstrates significant discrepancies with regard to the studied area. The analysis of new data on the thickness of the Earth's crust allowed us to identify the features of the deep structure of the lithospheric blocks associated with the large elements of the tectonic scheme of the territory of the Republic of the Niger.
Keywords: Republic of the Niger; gravitational field; stochastic interpretation; thickness of the Earth's crust